PENERAPAN PRINSIP HAK IMUNITAS ADVOKAT ATAS INTERPRETASI OBSTRUCSTION OF JUSTICE DALAM PERKARA PIDANA DI INDONESIA. - Niode, Mohamad Fajrin H; Farhana, Farhana; Dewi, Diah Sulastri (SENTRI: Jurnal Riset Ilmiah, 2024)
An advocate is a person whose profession is to provide legal services both inside and outside the court which fulfills the requirements based on the provisions of the law/the role and function of an advocate includes work carried out in court regarding criminal or civil law matters. Advocates cannot be prosecuted civilly or criminally. carry out their duties in good faith, namely to defend the client's interests in the trial process. These provisions expressly state the protection or immunity of advocates against all legal claims if they are carrying out their duties to accompany their clients on condition that they are based on good faith. According to the explanation of Article 16 of the Law on Advocates, what is meant by good faith is carrying out professional duties for the sake of upholding justice based on the law. Then the scope of this principle was expanded through the Constitutional Court decision Number 26/PUU-XI/2013. However, in criminal cases, advocates who defend their clients often commit acts aimed at obstructing and impeding the criminal justice process, known as obstruction of justice. The problem formulated is how does the principle of advocate immunity rights apply to the interpretation of obstruction of justice in criminal cases in Indonesia? What is the legal protection for advocates' immunity rights when defending their clients in criminal cases in Indonesia? To answer the problems above, the author uses legal research with a normative juridical approach. The type of legal research carried out in this research is normative juridical where law is conceptualized as what is written in statutory regulations (law in books) or law is conceptualized as rules or Norms are standards for human behavior that are considered appropriate. The approach applied is the Statute Approach and the Case Approach. The theories used in this research are the Law Enforcement Theory from Soerjono Soekanto, the Legal Protection Theory from Satjipto Raharjo and Philipus M. Hadjon, and the Professional Ethics Theory Advocate.The results of this research show that; The application of the principle of the Right to Advocate Immunity should not be interpreted excessively by an advocate, let alone as a shield in acting on behalf of a client who is in conflict with the law and not based on good faith. This is so vulnerable to being hit by legal violations such as obstruction of investigations or another term, Obstruction Of Justice. If it is proven that an advocate is not carrying out his duties in good faith, then the Law on Advocates and also the Code of Ethics for Indonesian Advocates will not protect his Immunity Rights. According to him, advocates in carrying out their profession are carried out carefully, carefully, alertly, and accompanied by high dedication, so that they become law enforcement figures who uphold the law, maintain the credibility and good name of the profession, and the most important thing is that every action taken must be based on good intention.